Kinship worldview : indigenous authors going deeper with holistic education - Freedman, Paul (Educator); Jacobs, Donald Trent, 1946- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Kinship Worldview: Indigenous Authors Going Deeper with Holistic Education is a collection of essays and poems offering testimony to the holism of original traditional indigenous ways of knowing, teaching and learning. Each chapter describes an Indigenous orientation to holistic education that explores deeply into the sacred interconnectedness of all life on Mother Earth. This collection from internationally recognized indigenous scholars and leaders reflects a "coherent worldview encompassing the processes of the world and how we humans find meaning in those processes" (Wildcat 2001, 7 - From Power and Place: Indian Education in America. Fulcrum Publishing). Indigenous worldview is the ultimate foundation for holistic education. Unfortunately, holistic education has been held back by post-colonial worlding, defined as the result of colonizing hegemony being intrinsic to most educational systems in dominant cultural schooling. As a result, implementation of this holistic ideal has fallen short of what we need to achieve in education. Here is a collection that returns to the roots of holism"--